COMMUNITY RESILIENCE IN HANDLING FLOOD DISASTER IN BOGOR CITY, WEST JAVA PROVINCE - Lubis, Bertha; Muslim, Muslim (Program Studi Manajemen Keamanan dan Keselamatan Publik IPDN, 2024)
Bogor City often faces the risk of natural disasters, such as floods, landslides, and strong winds. Community resilience in disaster management is a crucial factor in facing these challenges. This research aims to determine, describe, and analyze the Bogor City Regional Government in building community resilience in flood disaster management, specifically the steps taken by the local government in building community resilience in flood disaster management, and the challenges in building community resilience in disaster management in Bogor City. The research method used is the qualitative design with a descriptive method with data collected using interviews, observations, and taking sample criteria based on risk levels, geographic location, and participation in mitigation. The data were examined using Fuller’s resilience theory, namely anticipation, preparation, response, and adaptation. The research results showed that in the anticipation dimension through an early warning system (EWS) installed at various points, the community was able receive early warnings and take preventive actions. In addition, training programs such as SPAB and Disaster Resilient Villages. While in the preparation dimension, the community identified potential disasters in the residential environment by mapping local risks such as geographic conditions and infrastructure. The use of EWS and utilizing disaster history were also important to measure risk. After that, the preparation of a family evacuation plan must include identifying safe routes, gathering points, and routine evacuation simulations, so that each family member was ready to face an emergency situation and prepare communication using alternative communication tools such as radio or applications that do not depend on the telephone network. Furthermore, from the response dimension, the Bogor City community responded to the disaster with concrete actions such as independent evacuation and reporting to authorities via social media or emergency telephone numbers. Finally, in terms of adaptation, the community took concrete steps, such as building embankments as well as planning and evacuation. Keywords: Community Resilience, Disaster Management.